Relative melt viscosity, mechanical and electrical properties of polymer composites of HDPE/fly ash. - Hoàng, Thái; Đức, Vũ Minh; Giang, Nguyễn Vũ; Thẩm, Đỗ Quang; Quyền, Nguyễn Hồng (Vietnam Journal of Chemistry, 2012)
The polymer composites of HDPE/FA and HDPE/MFA (high density polyethylene/fly ash and modified fly ash) with different content of FA and MFA fillers were prepared by melt mixing in a Haake Rheomixer. The relative melt viscosity of the HDPE/FA and HDPE/MFA composites was increased with increasing FA and MFA content added into HDPE. The mechanical properties of the HDPE/FA and HDPE/MFA composites were lower than those of HDPE and decreased with increasing FA and MFA content. In comparison, the relative melt viscosity of those composites was smaller than the HDPE/FA composites and the HDPE/MFA composites had higher mechanical properties than HDPE/FA composites with the same content of the fillers. The electric properties (volume resistivity and dielectric strength) of the composites were also studied. The results showed that both FA and MFA decreased electric insulation of HDPE. However, the composites of HDPE/FA could be still good electric insulation materials.